Characterisation of Alzheimer's disease patients with agitation and their antipsychotic use: A study using the UK Clinical Practice Research Datalink: Managing dementia‐related behaviors. (7th December 2020) - Baker, Ross A; Lind, Stefan; Qizilbash, Nawab; Johnson, Michelle; Collings, Shuk‐Li; Bøg, Martin; Tran, Cam Thanh; Jørgensen, Kristian Tore
Abstract: Background: There are few data on patients with agitation in Alzheimer's disease (AD) and their use of antipsychotics (APs). This study characterised patients with agitation in AD (AAD) in terms of falls, and disease duration and examined their AP use compared to AD patients with other neuropsychiatric symptoms (NPS) and no NPS. Methods: Data from the UK Clinical Practice Research Datalink were analysed in two ways. Cross‐sectionally to characterise patients with AAD, other NPS and no NPS on 01/07/2016, using chi‐square and ANOVA for differences in proportions and means between groups, respectively. Retrospectively between 01/01/2015 and 31/12/2017 to compare AP use between AD patients with agitation, other NPS and no NPS using a Cox proportional hazards model adjusted for covariates. Results: At 01/07/2016, there were 10, 573 AD patients with a mean age of 83 years. Patients with AAD (n=605) had longer mean duration of disease (4.3 years) versus patients with other NPS (n=5102, 2.8 years) and no NPS (n=4772, 2.5 years) (p<0.001); more falls (53%) versus patients with other NPS (47%) and no NPS (33%) (p<0.001); were more likely to be prescribed atypical APs within last 60 days (24%) versus patients with other NPS (7%) and no NPS (4%) (p<0.001); and were more likely to have ever been prescribed benzodiazepine (64%) versus patients with other NPS (52%) and no NPS (24%) (p<0.001). During the 3‐year follow‐up, there were 24, 464 AD patients with median follow‐up of 1.1 years. The proportion of patients with an AP prescription during follow‐up was: 38% (AAD, n=2432), 20% (other NPS, n=13, 076) and 12% (no NPS, n=11, 816). Compared to patients with no NPS, the adjusted hazard ratio for AP use was 3.45 (95% CI 2.86‐4.17) for patients with AAD and 1.31 (95% CI 1.19‐1.44) for patients with other NPS. Conclusion: Patients with AAD are a particularly difficult to manage group. More patients with AAD had experienced falls and had a longer duration of AD than patients with other or no NPS. At the same time AP use was more than 3‐fold higher in patients with AAD than in patients without NPS.